Neuroprotective Effects of Grape Seed Extract against Cadmium Toxicity in Broilers - Al-awadhi, Rana M.; Kilany, Omnia E.; Abdallah, Osama M.; Naguib, Fatma M.; Nageh, Heba (Journal of applied veterinary sciences, 2024)
Ration contamination with cadmium chloride (CdCl2) leads to serious economic loss. The current study aimed to explain the ameliorative effect of grape seed extract (GSE) either alone or in combination with CdCl2. One hundred and fifty chicks were used in the current study. They were equally alienated into 6 groups; group I was kept as control. Group II: given grape seed extract by the first dose (GSE1) of 250 mg/kg; group III: given grape seed extract by the second dose (GSE2) of 500 mg/kg; group IV: given cadmium chloride (CdCl2) to evaluate the undesirable effects of the dose (100 mg/kg diet). Group V: given combination of GSE1+ CdCl2, group VI: given combination of GSE2+ CdCl2. At the end of the 3rd and 5th weeks, the following parameters were measured: Serum oxidants and antioxidants (GSH, SOD, CAT and MDA), brain oxidants and antioxidants (SOD, CAT, MDA, and NO), semi-quantitative RT-PCR detection of brain and liver GST and GPx, as well as serum cytokines (IL-1β, IL-10, and TNF-α), were determined. The results put on display show that GSE extract considerably ameliorated the levels of serum and tissue oxidants and antioxidants, as well as cytokines that ramshackle CdCl2. Histopathological assessment of brain tissue and BAX brain sections was in concurrence with the immunological, oxidant, antioxidant, and RT-PCR results. It is important to take into consideration that the immunostimulant, antioxidative properties of GSE are mechanistically achieved. So, GSE could be used as a protective agent against ration contamination.